IMPLEMENTASI METODE PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN FIQIH: STUDI KASUS DI MA ROUDLOTUL MUTAALLIMIEN - ABDUR ROHMAN; SIVIDINAL ISLAMIA; M. SUYUTI SHOLEH; AGUS NASIHUL AIMMAH; MOCH. TAUFIQURRAHMAN (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
The Team Games Tournament (TGT) type cooperative learning model has great potential to improve the quality of learning. Research shows that TGT has a positive effect on physical fitness, cooperative skills, and student learning outcomes. TGT encourages students to be active, collaborate and be responsible in the learning process. TGT is an alternative learning model that can be applied in various subjects to achieve more optimal learning goals. The Team Games Tournament (TGT) type cooperative learning model has great potential to improve the quality of learning. Research shows that TGT has a positive effect on physical fitness, cooperative skills, and student learning outcomes. TGT encourages students to be active, collaborate and be responsible in the learning process. This model consists of five stages: class presentation, group learning, games, tournaments, and team recognition. TGT is an alternative learning model that can be applied in various subjects to achieve more optimal learning goals.